Streptococcus pyrogens: A Short Review (International Journal of Scientific Research and Management (IJSRM), 2023)
Streptococcus pyrogens (commonly called as "group A streptococcus") is a pathogen infecting 18.1 million people and resulting in death of 5,00,000 people every year worldwide. The pathogens causing group A streptococcus (GAS) are commonly transmission through respiratory droplets, touching skin sore caused by GAS or through contaminated Material Streptococcus pyrogens is majorly found in children and elderly people. Preventing and controlling measures should be implemented to & reduce the risk of S. pyrogens by improving living Conditions and personal hygiene. GAS diseases are widely found in developing countries and low socioeconomic areas of developed countries.